Effects of training and taper on neuromuscular fatigue profile on 100-m swimming performance - Alves Ribeiro, F.; Dellavechia de Carvalho, C.; Causin Andreossi, J.; Miranda, D. R. M. (International Journal of Sports Medicine, 2023)
This study aimed to investigate the effects of 6-week specific preparatory period and 2-week taper period on neuromuscular fatigue profile in 100-m front crawl swimming performance. Seventeen competitive-level young-adult swimmers performed a 100-m swimming performance at baseline and after 6-week specific preparatory followed by 2-week taper periods. Neuromuscular fatigue profile was assessed through percutaneous electrical stimuli on the femoral nerve during a maximal voluntary contraction performed before and immediately after each 100-m maximal effort. Performance improved (p=0.001) 2.24 and 3.06% after specific and taper, respectively. Potentiated peak force at post-effort condition decreased (p<0.001) 16.26% at baseline, 11.70% at specific, and 12.86% at taper period. Maximal voluntary contraction force also decreased (p<0.001) at post-effort condition by about 6.77 and 9.33% at baseline and specific period, respectively. Both variables did not present significant differences between times. No condition or time effects were observed to superimposed peak force and voluntary activation, both related to central fatigue. In conclusion, neuromuscular fatigue during 100-m swimming performance was exclusively developed by peripheral mechanisms regardless of the training period, and 2-week taper was able to prevent decreases in maximal voluntary contraction induced by 100-m maximal effort.